The Effect of Product Diversification on the Purchase Decision of Telkomsel Loop Simcards (Case Study of Bandung State Polytechnic Students) - Henny Noviany (Fakultas Bisnis, 2020)
This study aims to determine and analyze the Effect of Product Diversification on the Purchase Decision of Telkomsel Loop Simcards (Case Study in Bandung State Polytechnic Students). The research method used in this research is a descriptive analysis and verification method with a population of 100 students by using accidental sampling technique by providing a link to fill out the questionnaire via Google Drive. The data analysis technique used is the Correlation Analysis Technique to determine the degree of closeness of the relationship between variables. The results showed that the direct effect of Product Diversification was 3.97. The indirect effect of the Purchasing Decision is 4.13. The test results are known to the constant value (a) of 2.537 and partially Product Diversification variable influences the Purchasing Decision variable. It was concluded that the effect of Product Diversification on Purchasing Decisions showed a positive regression coefficient of 0.468.